Giant Bilateral Adrenal Myelolipoma: Case Report - Roger, B. Rathna (Indian J Endocrinol Metab, 2020)
Adrenal myelolipomas are nonfunctional tumors that are usually asymptomatic; however, they have been known to coexist with other endocrine disorders, such as Cushing's syndrome, congenital adrenal hyperplasia (CAH), Conn's syndrome, and pheochromocytoma. We report a case of a 49-year-old man with hypertension and diabetes mellitus who complained of chronic abdominal pain, vomiting, and early satiety. Preoperative contrast-enhanced computerized tomography (CECT) was performed, and adrenal myelolipoma was considered, lab investigations revealed a nonfunctional tumor. CECT also revealed bilateral renal cortical cyst, right renal calculi, and hepatic cyst. A left open cortical sparing adrenalectomy was performed, pathological examination confirmed the diagnosis, and a radiological surveillance was planned for the right tumor. Four years following this, the patient came back with a similar presentation. Right adrenalectomy was performed after preoperative workup, and subsequently steroid replacement therapy was initiated. We suggest adequate follow-up of a patient presenting with adrenal myelolipoma and to explore the possibility of establishing a syndromic diagnosis such as autosomal dominant polycystic kidney disease (ADPKD).